The Digital Exclusion of People with Intellectual Disabilities During the COVID-19 Pandemic - Björnsdóttir, Kristín; Gunnarsdóttir, Hrafnhildur Snæfríðar- og; Gunnarsdóttir, Ellen Dröfn (Scandinavian Journal of Disability Research, 2024)
This article aims to explore whether and how people with intellectual disabilities in Iceland were using information and communication technology during periods of COVID-19-related social restrictions, as well as examine barriers to their access to and use of such technology. The study uses two sets of data. Survey data were collected from disabled people (n = 412) and data from focus group interviews with people with intellectual disabilities (n = 16) were used to expand and elaborate on the survey results. Contrary to previous research findings, socioeconomic status was not a significant barrier to digital access for the participants. However, the study’s results shed light on several intersecting socio-cultural hindrances that contributed to the digital exclusion of participants. The study is a contribution to a critical discussion on technological advancements, digital access, and uses that highlight the barriers derived from ableism.